FUNCTIONAL TRAINING IN OLDER AGE: BENEFITS FOR HEALTH AND QUALITY OF LIFE - Laerth Souza dos Santos Filho, Sandro (Health and Society, 2024)
Population aging is a global phenomenon that highlights the need for strategies to promote health and well-being for the elderly. Functional training emerges as a promising approach to improving health and quality of life in this age group, focusing on natural and functional movements. Older adults often face challenges related to loss of physical functionality, mobility problems and increased risk of falls. Functional training offers a holistic approach that can address these issues, promoting improvements in the physical, mental and social health of older people. Elderly people often face functional limitations, a decline in quality of life, and a greater propensity for age-related health conditions. The lack of exercise programs adapted to the needs of this population contributes to these problems, underestimating the importance of specific interventions for older adults. This study’s main objective is to investigate the effects of functional training in old age, evaluating its impact on improving physical functionality, reducing the risk of falls, mental well-being and the general quality of life of the elderly. Functional training is expected to promote significant improvements in muscular strength, balance, coordination and mobility in elderly participants. Furthermore, a reduction in the number of falls, improved mental well-being and increased autonomy and independence to carry out daily activities are expected.